The effect of geopolitical factors on local energy system performance: Examining the case of Palestine - Mahdi Abuhomos; Régis Delubac; Rémi Delage; Toshihiko Nakata (Energy Strategy Reviews)
Designing sustainable local energy systems requires addressing three aspects of the energy trilemma: energy economics, energy security, and environmental impact. These elements are influenced by geopolitical factors that exert policies over geographical locations in which the energy system operates. The geopolitics-energy nexus is typically studied in the context of global energy markets or energy challenges. However, this paper addresses the nexus from the perspective of sustainable local energy system design, focusing on the Israeli occupation's restrictions on Palestine's energy development. The methodology involves constructing an optimization model that aims to minimize annual costs while considering scenarios reflecting the occupation's restrictions. Preliminary estimations are made regarding energy demand loads and the potential supply from renewables. The assessment of renewable supply reveals promising figures for solar energy in Palestine, and demand estimations indicate that electricity consumption represents the highest demand among all energy carriers. The results demonstrate that geopolitical factors negatively impact the energy trilemma to varying degrees. Restrictions on Area C primarily affect energy security, while the West Bank-Gaza connection influences self-sufficiency and costs. Additionally, forced reliance on electricity imports impact all three pillars simultaneously. These limit the utilization of local renewable sources, thereby weakening energy sustainability. Furthermore, seasonal variations in demand intensify the impact of geopolitical factors. Integrating a 50 % electric vehicle into the transport system shows potential to mitigate these challenges, but it does not alter their effects. This research highlights the critical interplay between geopolitics and energy system design, providing insights into achieving energy sustainability under restrictive conditions.